IGF-Binding Protein 2 – Oncogene or Tumor Suppressor? - Pickard, Adam; McCance, Dennis J. (Frontiers in Endocrinology, 2015)
The role of Insulin-like growth factor binding protein 2 (IGFBP2) in cancer is unclear. In general IGFBP2 is considered to be oncogenic and its expression is often observed to be elevated in cancer. However, there are a number of conflicting reports in vitro and in vivo where IGFBP2 acts in a tumour suppressor manner. In this mini-review we discuss the factors influencing the variation in IGFBP2 expression in cancer and our interpretation of these findings.